PENGARUH SALURAN DISTRIBUSI LANGSUNG DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA PT. MAHSUN JAYA ONYX BAWEAN DI DESA KERTOSONO SIDAYU GRESIK - Maulidi, Ahib; Susetyorini, Susetyorini (Universitas Nusa Cendana, 2024)
This study aims to see the effect of direct distribution and promotion on customer satisfaction at PT. Mahsun Jaya Onyx Bawean. This study uses a Descriptive Method with a Quantitative Approach. The population in this study are all consumers at PT. Mahsun Jaya Onyx Bawean in 2021 totaling 98 people. Sampling in this study uses accidental sampling. The data source in this study is primary data using a research instrument in the form of a questionnaire. Data analysis used in this study includes validity and reliability tests, statistical tests, which consist of the coefficient of determination test, F-test, and t-test. Multiple regression tests, as well as classical assumption tests consisting of normality tests, heteroscedasticity tests, multicollinearity tests, linearity tests, and autocorrelation tests. The results of this study indicate that direct distribution and promotion variables have a significant influence on consumer satisfaction variables at PT. Mahsun Jaya Onyx Bawean. Keywords: Direct Distribution Channels; Promotions; Consumer Satisfaction